Pendampingan Peningkatan Kemampuan Menulis Penelitian Tindakan Kelas Guru Bahasa Inggris di Kabupaten Solok - Veni Roza; Absharini Kardena (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2021)
Increasing teacher competence should be carried out continuously. It is aimed to increase the professionalism of teachers in the field of teaching. One of ways that can be done to improve teacher pedagogical competence is by conducting Classroom Action Research (CAR). This research aims to improve the approach in teaching so that the results of student achievement can be improved. However, the implementation of CAR is often being an obstacle for teachers because of their lack of knowledge related to the implementation of CAR, which starts from the preparation of proposals, conducting research, to reporting research. It becomes a real urgency for teachers to get assistance in preparing CAR proposals as an initial step in implementing CAR in schools. An assistance for writing CAR proposals is a necessity for teachers so that the teachers have a strong basis for implementing CAR properly and correctly. Therefore, this assistance is carried out to improve the ability of teachers to write CAR proposals so that the final goal of implementing a good CAR can be realized